Empirical Analysis on the Preference of Negros Oriental State University Students to Online Shopping - Jaysone Christopher M. Bancoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
Online shopping has grown exponentially over the years together with the internet age. The COVID-19 pandemic further boosted this trend with its convenience attribute. It is projected that online shopping will continue to propel in the years to come. Thus, it is empirical to study the factors affecting the online purchase behavior of consumers. This study looks at the demographics, online shopping experience, and online shopping preference of Bachelor of Science in Business Administration students of Negros Oriental State University. A total of 319 valid responses were gathered and analyzed through descriptive approach There were more female respondents than male, mostly aged 20-23 years old. Almost all (93%) experienced online shopping, where clothes, accessories, footwears, beauty products, and electronic devices are the top products being purchased. 96% of the respondents also used cash-on-delivery as a method of payment. It was found that the perceived ease of use of the online shopping platform primarily drives online shopping among the respondents, followed by convenience, time saved, and security. Majority of the respondents prefer online shopping. Those who do not cited product quality risks and product delay as the reasons.